The Implementation of Public Transport Data Models in Hungary - Berki, Zs. (Acta Technica Jaurinensis, 2011)
The article focuses on the reasons behind the recent nationwide implementation of the European reference data model for public transport, TRANSMODEL and the service interface for real time information, SIRI in Hungary. It analyses the operational and institutional background, presents a brief introduction and their role in public transport management with application examples, particularly the liaison between TRANSMODEL and the location identification and coding rules of ELEKTRA Hungaria, the national chip card system.